Inducibility of interleukin-2 RNA expression in individual mature and immature T lymphocytes. - McGuire, K L (1987)
Expression of the gene for the T-cell growth hormone, interleukin 2 (IL2), is subject to at least two types of control. It is not only tissue specific, i.e. restricted to T lymphocytes, but also strictly dependent upon activation of the producing T cell. In mature cells, IL2 production is usually triggered via the cell surface receptor for antigen. To study the regulation of the murine IL2 gene in T-cell populations of differing stages of maturation, we have used a calcium ionophore in conjunction with the phorbol ester, TPA, to stimulate IL2 gene transcription while bypassing the requirement for triggering through a mature cell surface receptor. We have combined in situ hybridization with RNA probe protection analyses to quantitate accumulated cytoplasmic IL2 RNA and to identify the cells capable of inducing the IL2 gene in mature, immature and precursor T-cell populations. We report evidence for a distinction between the IL2 mRNA induction responses of different T cells, according to their maturation state and/or functional subclass. Mature splenic T cells that make IL2 can accumulate IL2 transcripts to more than 100 copies per cell. However, we find that many T-lineage cells, especially in immature populations, show induction-dependent IL2 gene expression but only accumulate low levels of IL2 mRNA per cell.